Letter : Family Urrutia - Pye, Edith M. (Edith Mary)
1940-04-02 038-0047-002 COMMISSION INTERNATIONALE D'AIDE AUX ENFANTS RÉFUGIÉS INTERNATIONAL COMMISSION FOR THE ASSISTANCE OF CHILD REFUGEES EN COLLABORATION AVEC AMERICAN FRIENDS SERVICE COMMITTEE (American Quakers) Philadelphia FRIENDS SERVICE COUNCIL (English Quakers) London SERVICE CIVIL INTERNATIONAL Berne UNION INTERNATIONALE DE SECOURS AUX ENFANTS, Genève PRÉSIDENT JUDGE MICHAEL HANSSON Ancien Président de l'Office International Nansen, à Genève VICE-PRÉSIDENTS THE Rt. HON. VISCOUNT CRANBORNE, M.P. London MADAME G. MALATERRE SELLIER, Paris PROFESSOR BERTIL OHLIN, Stockholm MADAME E. CHEVALLEY, Paris VICE-PRÉSIDENT ET DIRECTEUR HOWARD E. KERSHNER SECTION FRANÇAISE : Bureau 418 30, Rue de Gramont, PARIS -2. SECTION ESPAGNOLE : Bureau 406 Addresse Télégraphique : ICFAR - PARIS Téléphone: RICHELIEU 80-80 à 85 44, Upper Park Road, N.W.3. 2nd April, 1940. H. Tewson, Esq., International Dept. Trade Union Congress, Transport House, S.W.1. Dear Mr. Tewson, Re: Family Urrutia. I have just received the enclosed letter from Miss Esme Odgers which will set the mind of the father of these children at rest. The children are being paid for by the International Commission and cared for through the Foster Parents Plan. As their mother is with them in the character of a helper, I think that is is a very satisfactory arrangement. Yours sincerely, E M Pye E.M. PYE. 292/946/38/47(II)